Clinical Findings in an Asian Family with Axenfeld-Rieger Syndrome: Doi: 10.36351/pjo.v36i2.974 - Rebecca, Rebecca; Junejo, Murtaza Sameen; Jamil, Syed; Junejo, Sameen Afzal (Pakistan Journal of Ophthalmology, 2020)
A case of 46-year-old male is presented who came with complaints of painless, progressive deterioration of vision in both eyes and he was using Latanoprost and Cosopt eye drops in both eyes. His visual acuity was 6/60 in right eye and perception of light in left eye. The intraocular pressures were 28?mm?Hg (OD) and 18?mm?Hg (OS). There was iridocorneal adhesion and posterior embryotoxon in his right eye and leucoma in left eye. Cup-disc ratio was 0.7. He had hypodontia, midface hypoplasia, hypertelorism, and telecanthus. Family history was also positive. His sister also had iris stromal hypoplasia along with posterior embryotoxon. A diagnosis of Axenfeld Rieger Syndrome was made The patient underwent glaucoma drainage devise (AGV) surgery in his right eye. Post operative pressures were 10mm Hg. He was later referred to maxillofacial surgeon, cardiologist and counseled for avoiding cross marriages to prevent this inherited disease